The interplay between Helicobacter pylori, gastro-oesophageal reflux disease, and intestinal metaplasia. (11th February 2005) - Malfertheiner, P; Peitz, U
Abstract : Helicobacter pylori infection and gastro-oesophageal reflux disease (GERD) account for most upper gastrointestinal pathologies with a wide spectrum of clinical manifestations. The interplay of both conditions is complex, in part intriguing, and has become a matter of debate because of conflicting results. The cardia is an area where both H pylori and abnormal GERD exert their damaging potential, inducing inflammation and its consequences, such as intestinal metaplasia. While the role of intestinal metaplasia within columnar lined epithelium (Barrett's oesophagus) in the context of GERD is well established as a risk for neoplasia development, the role of intestinal metaplasia at the cardia in the context of H pylori infection is unclear. A particular challenge is the distinction of intestinal metaplasia as a consequence of GERD or H pylori if both conditions are concomitant. Available data on this issue, including follow up of a small patient series, are presented, but more studies are required to shed light on this issue because they will help to identify those patients that need surveillance.